SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN PILIHAN PEKERJAAN DENGAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) - Mahmudi, A. Aviv (potensio, 2013)
Applying the Analytical Hierarchy Process ( AHP ) , required the selection criteria and alternatives , and calculate the weight of a survey questionnaire to decision-makers or users of the system in a place / location associated with the object to be careful . After that , test the consistency necessary to test the validity of the results obtained , and define alternative with the greatest weight as an option . Analytical Hierarchy Process ( AHP ) is able to analyze the selection criteria so as to produce the best ranking in a decision support system determination of employment options . Expert choise is a software that can be used to implement the AHP method . After doing the calculations manually and detail , obtained scores of weight composite PT